Thermoelectric power properties of hydrogenated alloy Ti-6Al-4V subjected to mechanical impact and electron irradiation; Technical Physics; Vol. 69, No. 5 - Larionov V. V. Vitaliy Vasilyevich (2024, 2024)
Title screen